Analisa dan Perancangan Sistem Pelaporan Kinerja Pegawai Menggunakan Work System Framework dengan Pemodelan UML - Erid Ade Putra (INTECOMS: Journal of Information Technology and Computer Science, 2018)
Employee performance report is an important element in an organization. This report relates to activities undertaken by employees in accordance with their respective duties and the amount of allowances earned employees within one month of work. General Bureau is one of the agencies that require employee performance report where at this moment this report is still done manually. For that, needed a system in managing employee performance report. The system built is analyzed using work system framework method, to model the system to be built then used unified modeling language. Keywords: Analysis and design, work system framework, unified modeling language, employee performance reporting application